Variation of African horsesickness virus nonstructural protein NS3 in southern Africa - van Niekerk, M.; van Staden, V.; van Dijk, A. A.; Huismans, H. (Journal of General Virology, 2001)
NS3 protein sequences of recent African horsesickness virus (AHSV) field isolates, reference strains and current vaccine strains in southern Africa were determined and compared. The variation of AHSV NS3 was found to be as much as 36·3% across serotypes and 27·6% within serotypes. NS3 proteins of vaccine and field isolates of a specific serotype were found to differ between 2·3% and 9·7%. NS3 of field isolates within a serotype differed up to 11·1%. Our data indicate that AHSV NS3 is the second most variable AHSV protein, the most variable being the major outer capsid protein, VP2. The inferred phylogeny of AHSV NS3 corresponded well with the described NS3 phylogenetic clusters. The only exception was AHSV-8 NS3, which clustered into different groups than previously described. No obvious sequence markers could be correlated with virulence. Our results suggest that NS3 sequence variation data could be used to distinguish between field isolates and live attenuated vaccine strains of the same serotype.